274 Malignant germ cell tumors patients between 14 – 39 years, a 3 decades experience in a public hospital 1985 – 2015 san borja arriaran hospital. (18th September 2019) - Altamirano, R; Nazzal, O; Suarez, E; Acosta, P
Abstract : Objectives: Describe malignant germ germ cell tumors of the ovary in patients, between 1985 - 2015 at San Borja Arriaran Hospital (HCSBA) in Santiago, Chile. HCSBA is a public institution that covers about 20% of the chilean capital population. Methods: Retrospective search in the gynecology oncology and pathology HCSBA units data bases of the following parameters; histology type and age of initial diagnostic. We found a total of 19 records of female patients with malignant germ germ cell tumors between 14–39 years, that were reviewed and analyzed by 3 members of our unit. Results: The most frequent histology was dysgerminoma (58%), followed by Immature teratoma (21%), mixed germ cell tumors (16%) and yolk sac tumor (5%). 53% of our cases were in patients between 14–20 years old and only 16% older than 30 years. Conclusions: Our findings were similar as those founded in the international literature in prevalence and age related incidence, but we found an increased incidence in Disgerminoma. We are unable to analize treatments, because of the variation in the last 3 decades. We can agree that overall survival was related with early stage diagnostic and improved in the last 20 years with the incorporation of adequate chemotherapy, surgical staging and precise pathology techniques.